Metode Pengering Gabah Aliran Massa Kontinu Sebagai Pengering Alternatif Pada Musim Penghujan Dengan Sumber Energi Dari Cahaya Lampu Mono Kromatis - Nusyirwan Nusyirwan (METAL: Jurnal Sistem Mekanik dan Termal, 2018)
In the rainy season, rice grain from the harvesting field cannot be dried properly. This condition is due to sunlight being blocked up by the cloud therefore the sunlight intensity on the earth surface is small. As a consequence many farmers become loss because this low quality rice is sale at a lower price. To overcome the above problems, it is necessary to make a dryer that not directly depend on the solar energy. In this research, a method for rice drying using light from monochrome lamp is proposed. The dryer consist of a silinder-shaped container which is equipped whith a stirer that can be adjusted according to the desired speed. In the drying chamber, hot air that regulated in the drying room is produced by incandescent lamp. The drying result obtained from this dryer using 40 rpm rotation speed reaches an absolute dry percentage of rice at equivalent of 14 %. While for stirrer rotation 50 rpm and 60 rpm the drying percentage is 8 % and 5 %. From these results, it can be concluded that the best condition for the drying process is obtained for stirrer rotation speed 40 rpm.